2013
DOI: 10.2494/photopolymer.26.217
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar Low-bandgap Copolymers Consisting of Dithienoketopyrrole for All-Polymer Solar Cells

Abstract: The new low-band gap copolymers containing electron-accepting thienoisoindigo (TIDG) exhibit the low-lying lowest unoccupied molecular orbital (LUMO) at-3.8 eV. This envisions their use as n-type polymer in combination with typical p-type regioregular poly(3-hexylthiophene) (P3HT) towards all-polymer organic photovoltaics (OPV). The alternating fluorene and TIDG copolymer, PFTIDG, shows the electronic absorption maximum at 744 nm in the film states, of which spectrum is complementary to that of P3HT and thus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In contrast, thienoisoindigo (TII), in which the benzene rings of the II unit are replaced with thiophenes, is a completely planar unit since the non-bonding sulfur-oxygen interaction removes the steric hindrance to form a at p-surface and enhance the charge delocalization coming from the quinoidal structure of the framework. 8,[23][24][25][26][27][28][29][30][31][32][33][34][35] In a previous study, we reported ambipolar TII-based small molecules, and these molecules displayed wellbalanced hole and electron mobilities of 10 À2 cm 2 V À1 s À1 in spite of the one-dimensional p-system. 28 These results prompted us to design a more p-expanded TII-based molecule, benzothienoisoindigo BTII, to ensure strong p-p intermolecular interactions constructing a dense molecular packing preferable for effective charge-transport.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, thienoisoindigo (TII), in which the benzene rings of the II unit are replaced with thiophenes, is a completely planar unit since the non-bonding sulfur-oxygen interaction removes the steric hindrance to form a at p-surface and enhance the charge delocalization coming from the quinoidal structure of the framework. 8,[23][24][25][26][27][28][29][30][31][32][33][34][35] In a previous study, we reported ambipolar TII-based small molecules, and these molecules displayed wellbalanced hole and electron mobilities of 10 À2 cm 2 V À1 s À1 in spite of the one-dimensional p-system. 28 These results prompted us to design a more p-expanded TII-based molecule, benzothienoisoindigo BTII, to ensure strong p-p intermolecular interactions constructing a dense molecular packing preferable for effective charge-transport.…”
Section: Introductionmentioning
confidence: 91%
“…14,15 However, the ambipolar properties of small molecules are still lower than those of polymer semiconductors. 8,[23][24][25][26][27][28][29][30][31][32][33][34][35] In a previous study, we reported ambipolar TII-based small molecules, and these molecules displayed wellbalanced hole and electron mobilities of 10 À2 cm 2 V À1 s À1 in spite of the one-dimensional p-system. [16][17][18][19][20][21] Among the building blocks constituting organic semiconductors, isoindigo (II) is well known as an electron-decient unit realizing a high performance OFET.…”
Section: Introductionmentioning
confidence: 99%
“…Xe-flash time-resolved microwave conductivity (Xe-TRMC, 9 GHz) 27) experiment using a pseudo-sunlight white light pulse (0.3 mJ cm -2 pulse -1 ) as an excitation was conducted in order to study the photovoltaic performance of polymer: [6,6]-phenyl-C 61 -butyric acid methyl ester (PC 61 BM, purchased from Frontier Carbon Inc.) blends prior to device fabrication. 24,[28][29][30][31] The blend samples were prepared by drop-casting chlorobenzene (CB) solution of polymer:PC 61 BM onto quartz plate and dried under vacuum. The photoconductivity was obtained by P r /AP r , where P r , A, and P r , are the transient power change of reflected microwave power, sensitivity factor, and reflected microwave power, respectively.…”
Section: Synthesis Of Btt-mentioning
confidence: 99%
“…TIDG demonstrates a high planarity and strong electron affinity in nature, which allows extending photoabsorption to near infrared region [15], and thus, TIDG is attempted to be coupled with various donor units [20][21][22][23]. The constrained low PCEs are partly ascribed to the short lifetime of singlet exciton [16] associated with energy gap law [24].…”
Section: Idg Tidg Btidgmentioning
confidence: 99%